ASAS-ASAS PENYELENGGARAAN NEGARA PESPEKTIF UNDANG-UNDANG DAN HUKUM ISLAM - Aminullah, Muhammad Soleh; Majid, Nur Julian (Mitsaqan Ghalizan, 2024)
In this era of ongoing reform, governance still leaves various problems. Especially those related to efforts to improve the quality of good and clean governance are still far from what is expected. This research is a descriptive-analytical normative legal research (legal research) with a statutory approach and is sourced from primary sources, namely laws, books and other supporting literature. The research shows that based on the principles of state administration, there are deviations made by state administrators with what is expected. State organizers go out of the line that has been set by the law and (rules) of religion that should be used as guidelines in the implementation of good governance as a form of responsibility in the world and the hereafter.